MASALAH-MASALAH YANG DIALAMI SISWA SD SEKECAMATAN RUMBIO JAYA T.P 2015/2016 - Nurazmi '; Tri Umari; Rosmawti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The objectives of this study are 1) to get the description about personal problem experienced male and female students 2) to get the description about emotional problems experienced by male and female students, 3) to get the information about learning problems experienced by male and female students, 4) to get the information about family problems experienced by male and female students, 5) to get the information about social problem experienced by male and female students, 6) to get the descriptions about the problems of male and female students in some aspects such as personal, emotional learning, family and social, 7) to get the description about the problems experienced by male and female students in general. The population of this research is all of the students in class IV and V of School in Rimbo Jaya, they are Elementary School Number 009 Teratak that consists of 37 students and Elementary School Number Number 001 Teratak that consist of 121 students, and Elementary School Number 004 Pulau Payung that consists of 62 students. So, the total population in this research is 220 students of class IV and V Elementary Schools in Rimbo Jaya Sub District Academic Year 2015/2016. The technique of collecting data is total sampling that means all of the population are the members of the sample. The results shows that 1) the personal problems experienced by male students is 58 (51%) and female students is 50 (47%) included in middle category, 2) the personal problems experienced by male students is 49 (43%) included in few category and female students is 60 (56%) included in middle category, (3) the learning problems experienced by male students is 71 (63%) included in middle category and female students is 61 (57%) included in middle category, 4) the family problems experienced by male students is 75 (66%) included in few category and female students is 76 (71%) included in few category, 5) the social problems experienced by male students is 75 (66%) in few category and female students is 64 (60%) included in few category, 6) the problems that experienced by male and female students are in several aspects such as personal aspect, emotional aspect, learning aspect, family aspect and social aspect experienced by male and female students is social problem is 151 (69%) in few category, 7) In general, the problem that experienced by male and female students included in many category is learning problems especially in learning achievement, that are 37 students (17%).Keywords: Problems